The effect of different sweeteners in low-calorie yogurts - a review - Pinheiro, MVS; Oliveira, M. N.; Penna, ALB; Tamime, A. Y. (Blackwell Publishing, 2005)
Recently, increased demand for low-calorie products and foods with alternative sweeteners has gained special attention. Intense sweeteners avoid the problems of health risks associated with caloric sweeteners. This paper presents information about the technical characteristics of the more widely used artificial sweeteners and the possibility of their application in low-calorie yogurts.
Keywords: artificial sweeteners; low-calorie; yogurt